ʻĀina as resilience: mapping community networks and collaborative care in Hawaiʻi - Mahi, Dawn; Su, Kaiqing; Santiago, Reinier Paul; Kim, Emi; Vaughan, Mehana; Connelly, Sean (Frontiers in Sustainability, 2024)
This article examines the growth of Indigenous grassroots community groups across Hawaiʻi, whose efforts are pivotal to place-based climate change resilience and community well-being. Instead of focusing on specific ecosystem resilience actions, it highlights the people and places that make this movement of community organizations resilient, leveraging both social and cultural strengths to adapt to climate impacts. For many Indigenous peoples, climate change is not new; adaptation has already been integral to relationships between environment and culture. These changes require culturally responsive approaches, not short-term engineering solutions such as coastal hardening or stream channelization. A collaboration between a grassroots artist mapping initiative ('ĀINAVIS) and a university's community-based research project ('ĀINA KUPU), this study utilizes a novel data index compiled using publicly available information to inform a series of in-depth student interviews with community groups across Hawai'i whose mission, vision, and work are dedicated to caring for 'āina. We find that these "ʻĀina Organizations" articulate climate resilience in multi-faceted and culturally grounded ways, maintaining reciprocal and mutual relationships with ʻāina, the Hawaiian term for land meaning